ANALISIS FRAMING DALAM PEMBERITAAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90PUU-XXI2023 DI MEDIA INDONESIA - Ramadhani, Rizky Wulan; Bramantyo, Bagus Dwi; Pitoyo (Kinesik, 2024)
Media Indonesia has an ideology that impacts the framing of reporting on the Constitutional Court decision Number 90/PUU-XXI/2023 regarding the age limit for presidential candidates and vice-presidential candidates on October 16, 2023. This research aims to determine the framing carried out by Media Indonesia in reporting the Constitutional Court decision Number 90/PUU-XXI/2023 with a framing analysis of the Pan and Kosicki model. Researchers analyzed news articles with “Putusan MK” from October 22 to November 2, 2023. This research shows that Media Indonesia emphasizes the impact of legal legitimacy. Based on the syntactic structure, the structure of the news begins with the object and problem and forms the event systematically. Based on the script structure, the reporting carried out by Media Indonesia contains elements of 5W+1H. Based on the thematic structure, Media Indonesia presents broad news themes regarding the Constitutional Court's decision and the nomination of Gibran Rakabuming as vice presidential candidate in the 2024 elections. Based on the rhetorical structure, Media Indonesia's discourse follows the facts and leads to the ethics of alleged violations. Media Indonesia's cover photo frame in the news does not use photos or images that corner one of the parties.